Emerging therapeutic options for periorbital and orbital cutaneous basal and squamous cell carcinomas. (4th March 2023) - Wladis, Edward J.; Wrzesinski, Stephen H.; Rothschild, Michael I.; Adam, Alejandro P.
ABSTRACT: Purpose: Recently, several new therapies have emerged to address locally advanced cutaneous basal cell and squamous cell carcinomas. Given the constraints of the ocular adnexa and orbit, this review was designed to discuss the role of these modalities in this region. Methods: A PubMed search was carried out to analyze the utility of United States Food and Drug Administration-approved therapies to address these malignancies. The data presented in the identified investigations were analyzed and abstracted. Results: Multiple novel interventions may be useful in the management of periocular cutaneous basal cell and squamous cell carcinomas, including imiquimod, hedgehog inhibitors, and immunotherapy. While many of these treatments have not been specifically explored in the orbit and ocular adnexa, the literature generally shows favorable response rates. However, adverse events were common in these studies. Conclusions: Several novel treatments may address periorbital cutaneous malignancies, and these therapies may be particularly useful in patients with unresectable disease and those who are poor surgical candidates.